(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
«Kalila and Dimna» is a monument of didactic literature, a kind of mirror for the feudal ruler, teaching him how to rule justly. In terms of composition, the book goes back to ancient Indian literature Plot borrowings from «Kalila and Dimna» were widely used in European, including Russian literature (fables by La Fontaine and Krylov, «The Frog Traveller» by Garshin, fairy tales-fables by L. Tolstoy, etc.).